2017
DOI: 10.2147/ott.s127738
|View full text |Cite
|
Sign up to set email alerts
|

Holliday junction–recognizing protein promotes cell proliferation and correlates with unfavorable clinical outcome of hepatocellular carcinoma

Abstract: AimTo investigate the expression and clinical significance of Holliday junction–recognizing protein (HJURP) in hepatocellular carcinoma (HCC).MethodsIn this study, we detected the expression of HJURP protein in samples of 164 patients with HCC, and based on this, we divided the patients into two cohorts: high expression of HJURP and low expression of HJURP. We analyzed the correlation between HJURP expression and the clinicopathological factors using chi-square test. Survival significance of HJURP was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 20 publications
3
39
0
Order By: Relevance
“…Other studies have described the association between HJURP overexpression, combined with additional alterations, and a higher risk of death for GBM patients (de Tayrac et al, 2011;Valente et al, 2013). Moreover, it was also reported that HJURP overexpression has an independent prognostic value for breast (Hu et al, 2010), lung (Kato et al, 2007), liver (Hu et al, 2017) and ovarian cancer patients, reinforcing the involvement of this protein with cancer aggressiveness and poor outcome.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 84%
“…Other studies have described the association between HJURP overexpression, combined with additional alterations, and a higher risk of death for GBM patients (de Tayrac et al, 2011;Valente et al, 2013). Moreover, it was also reported that HJURP overexpression has an independent prognostic value for breast (Hu et al, 2010), lung (Kato et al, 2007), liver (Hu et al, 2017) and ovarian cancer patients, reinforcing the involvement of this protein with cancer aggressiveness and poor outcome.…”
Section: Dna Repair Genes As Biomarkers Of Astrocytoma Aggressivenessmentioning
confidence: 84%
“…HJURP has been demonstrated to play an important role in human neoplasms [ 7 9 , 25 ]. HJURP exhibits oncogenic activity in various cancer types including HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, HJURP has been reported to be highly expressed in some malignancies, including HCC, breast cancer, lung cancer, bladder cancer and glioma [ 6 11 ]. Hu et al found that HJURP promotes cell proliferation in vitro and that its expression is correlated with unfavorable clinical outcomes in HCC [ 9 ]. Moreover, Huang et al demonstrated that a single nucleotide polymorphism (SNP) of HJURP, i.e.,rs3771333, can predict a higher susceptibility to HCC among Chinese people [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, activation of HJURP is required for chromosomal stability and is also involved in immortalizing cancer cells [ 7 ]. The aberrant upregulation of HJURP has been reported in several human cancers, including breast cancer [ 9 , 10 ]. These findings support the role of HJURP as both a prognostic biomarker and also as a potential novel therapeutic target for the development of anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…HJURP has dual roles in DNA repair and chromosome segregation during mitosis, and the ectopic activation of HJURP has been shown to be associated with the immortality of cancer cells [ 7 ]. Overexpression of HJURP has now been reported in hepatocellular carcinoma and breast cancer [ 9 , 10 ]. However, there remains limited understanding on whether HJURP expression is a prognostic biomarker in ovarian cancer, despite continuing reports of HJURP in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%